Review of The Completeness of Filling In The Form (CPPT) of The Inpatient Midwifery Ward of Aisyiyah Hospital - Rahmadhani Rahmadhani; Dewi Mardiawati; Oktamianiza Oktamianiza; Heru Rahmat Wibawa; Yopia Priyanti; Siti Handam Dewi (Universitas Duta Bangsa Surakarta, 2026)
Incompleteness of Inpatient (CPPT) form affects the quality of medical records in hospitals. The (CPPT) form must be filled out completely to improve the quality of hospital services and can be accounted for if there are errors in service, action or medication administration. The purpose of this study was carried out because there are still many problems found related to incompleteness of the (CPPT) form by PPA at Aisyiyah Hospital. The study was conducted at Aisyiyah Hospital from January to March 2025, this type of research is quantitative research with a descriptive approach. The population was 144, with the Accidental Sampling sample technique, obtained 59. Data processing techniques were editing, coding, processing, and cleaning. The results of the study obtained a percentage of identification data as much as 1 (1.7%) incomplete 58 (98.3%) complete, in important reports 17 (28.8%) incomplete 42 (71.2%) complete. In authentication 50 (84.7%) incomplete 9 (15.3%) complete. In good record keeping, 21 (35.6%) were incomplete, 38 (64.4%) were complete. In filling out the form (CPPT), 51 (86.4%) were incomplete, 8 (13.6%) were complete. This was due to a lack of awareness among officers in filling out the CPPT form. The conclusion in this study was that incompleteness was still found, especially in the Authentication and Completion of the CPPT Form. This has an impact on patient safety and the accountability of medical personnel. It is recommended that officers fill out the CPPT form completely and accurately to support safe and quality health services.